Palliative Procedures in Lung Cancer - Masuda, Emi; Sista, Akhilesh K.; Pua, Bradley B.; Madoff, David C. (Seminars in Interventional Radiology, 2013)
Palliative care aims to optimize comfort and function when cure is not possible. Image-guided interventions for palliative treatment of lung cancer is aimed at local control of advanced disease in the affected lung, adjacent mediastinal structures, or distant metastatic sites. These procedures include endovascular therapy for superior vena cava syndrome, bronchial artery embolization for hemoptysis associated with lung cancer, and ablation of osseous metastasis. Pathophysiology, clinical presentation, indications of these palliative treatments, procedural techniques, complications, and possible future interventions are discussed in this article.
Keywords: palliative treatment; superior vena cava (SVC) syndrome; hemoptysis; osseous metastasis; interventional radiology